ECG simulator for testing and servicing cardiac monitors and electrocardiographs - De Lucena, Samuel E. [UNESP] (My University, 2011)
This paperwork presents the design and test of a microcontroller-based ECG (electrocardiogram) simulator. The ECG simulator is capable of generating nine ECG signals and a calibrated square wave (1 Hz, 1 mV at Lead II). The synthesized signals are: normal sinus rhythm (60 beats per minute - BPM, and 90 BPM), sinus bradycardia (30 BPM), sinus tachycardia (120, 180 and 240 BPM), sinus rhythm with tall T wave (6EC0 BPM), ventricular tachycardia (120 BPM), and a rhythm for asynchronous ventricular pacemaker (60 BPM). The simulated ECG signals can have their amplitudes continuously varied from zero to 2 mV at lead II, through a panel potentiometer, whose knob position does not affect the amplitude of the square wave calibrated signal. The technique used to synthesize the ECG signals, a modified direct digital synthesis (DDS), appeared superior in permitting the generation of signals of very good quality and yet using a relatively small amount of memory. This latter feature enabled the use of a simple 8-bit microcontroller together with an external precision D/A converter and a 2-pole low-pass active filter. The designed ECG simulator can be a handsome instrument to daily ECG machine test, maintenance and demonstration by hospital personnel and medical equipment maintenance groups and shops.
Keywords: Cardiac monitor; ECG simulators; Electrocardiographs; Maintenance; Medical instrumentation